ANALYSIS OF CONSUMER PREFERENCES AND SATISFACTION WITH BULOG RICE SALES IN ALAM BARAJO DISTRICT, JAMBI CITY - tamara, vidiya; Suandi, Suandi; Effran, Endy (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2023)
ABSTRACT The increasing competition in the rice market in Indonesia encourages the importance of understanding consumer preferences and satisfaction levels for rice sold by the Logistics Affairs Agency (Bulog). This study aims to (1) describe the socio-economic situation of Bulog rice consumers in Alam Barajo District, Jambi City, (2) to analyze consumer preferences and satisfaction with Bulog rice, and (3) to analyze socio-economic influencing factors on Bulog rice consumer preferences. The research was conducted in Alam Barajo District, Jambi City. The research was conducted for three calendar months. The data used were primary data and secondary data with a total of 50 respondents. The data was analyzed by means of statistical tests by regression method and satisfaction test. The results of consumer research have a high level of satisfaction and interest in Bulog rice, Importance Performance Analysis (IPA) analysis of rice attributes that are included in the main priority quadrant (I) are cleanliness, texture and price. The attribute that is included in the quadrant that maintains its achievement (II) is endurance. The attributes included in the low priority quadrant (III) are the aroma and integrity and uniformity of rice.The attributes included in the satisfactory quadrant (IV) are color and distribution services. The Customer Satisfaction Index (CSI) analysis results of the satisfaction index obtained are 0.7767 which means it is in the satisfied category. Consumer preferences are influenced by income, number of family members, amount of household expenses, and employment while those that do not affect preferences are age and education.